Learning from the Bangladeshi Islamic Microfinance Model for Sharia Microfinance Development in Indonesia - Adinda Rizqi Nur Azizah; Amin Wahyudi; Raisha Salisa Ahmad (El-Barka Journal of Islamic Economics and Business, 2025)
The extreme institutional fragmentation of Indonesia's 4,500+ BMT units has led to an inability to achieve economies of scale despite serving 3.7 million customers with assets of Rp 16 trillion, while the Bangladesh centric bank model (RDS-IBBL) serves 520,000 members with high efficiency but at the expense of social closeness, creating a trade-off of efficiency versus embeddedness that requires systematic investigation. The research uses a comparative qualitative method by analyzing academic literature 2008-2025, institutional reports (UNDP, Bangladesh Bank, OJK, LAZ), and regulatory documents through comparative descriptive analysis of six dimensions with multi-source triangulation validity. Empirical findings show that the Bangladesh bank-centric model achieved a recovery rate of >95% and increased the income of 72% of participants, while the Indonesian community-based model had a recovery rate of 85-90% but was resilient during the 1997-1998 crisis, with a dominance of 70-80% in both countries, explained five factors: transaction cost economics, extreme information asymmetry, institutional path dependency, regulatory constraints, and customer preference for certainty. The theoretical contribution validates the path dependency theory that institutional design shaped by historical trajectories is different (the legacy of the Grameen Bank versus the tradition of mutual cooperation) and rejects the assumption of convergence by proving persistent diversity that is context-dependent. The policy implications include five recommendations: a national apex body BMT for shared services while preserving local autonomy; Sharia Microfinance Academy with a target of 5,000 certified professionals in 5 years; harmonization of OJK regulations, Ministry of Cooperatives, Ministry of Religion; dual-track financing strategy to increase PLS proportion from <20% to 40% in 5 years; and the Structured Waqf Zakat Microfinance Integration Model Graduated Approach (70-80% Mustahiq to become muzakki in 2-3 years), requires a national coordination framework to transform the MFI ecosystem from atomistic fragmented to networked professionals to contribute optimally to the SDGs.